DIETARY STRATEGIES FOR MANAGING OBESITY AND POLYCYSTIC OVARY SYNDROME (PCOS) - da Cruz, José Ribamar Sousa (Revista Sistemática, 2024)
Obesity and polycystic ovary syndrome (PCOS) are often interrelated conditions, both exacerbated by insulin resistance and hormonal imbalances. Managing these conditions requires a multidisciplinary approach, with dietary interventions playing a central role. Two common dietary strategies explored for weight management in PCOS are hypocaloric and ketogenic diets, each with distinct mechanisms and benefits. Hypocaloric diets focus on reducing daily caloric intake, promoting gradual and sustainable weight loss, which can improve insulin sensitivity and reduce androgen levels, alleviating symptoms such as menstrual irregularities and acne. However, weight loss may be slower, and these diets do not directly address insulin resistance. On the other hand, ketogenic diets involve drastically reducing carbohydrate intake and increasing fat consumption, inducing ketosis, and leading to rapid weight loss. This approach has shown significant benefits for women with severe obesity and insulin resistance, improving metabolic markers like glucose and cholesterol levels and enhancing hormonal balance. However, the restrictive nature of the ketogenic diet may make long-term adherence difficult, and side effects such as “keto flu” can hinder its success. Research studies have demonstrated that both diets can be effective in managing PCOS, with the ketogenic diet offering faster results and the hypocaloric diet providing long-term benefits. Ultimately, the choice between these dietary strategies should be personalized, taking into account the patient’s metabolic profile, preferences, and health goals. Continuous professional monitoring is essential to ensure nutritional adequacy and prevent complications. A holistic, individualized approach, combining diet, exercise, and medical supervision, is essential for effectively managing obesity and PCOS.